Perovskite film, preparation method thereof and perovskite solar cell
By using methyl ammonium halide solution and a solution containing formidine halide salt for exchange treatment during the preparation of perovskite film, the homogenization of monovalent cations is promoted by linear alkyl ammonium halide, and the monovalent perovskite monovalent is solved by using linear alkyl ammonium halide. The problem of uneven cation distribution improves the performance of perovskite film and the conversion efficiency of solar cells.
Patent Information
- Application Number
- CN202411739005.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-11-28
AI Technical Summary
During the synthesis of perovskites in the water system, the monovalent cations of perovskites are unevenly distributed, which affects the final membrane performance.
By placing the divalent inorganic salt film in a methyl ammonium halide solution for soaking and exchanging treatment with a solution containing a formidine halide salt during the annealing process, the formidine ion and methylamine are promoted by linear alkyl ammonium halide. Ion homogenization.
The uniform distribution of monovalent cations in the perovskite film is achieved, the grain size is improved, the charge trap density is reduced, the carrier life is extended, and the conversion efficiency of solar cells is improved.
Smart Images

Figure CN119451526A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of solar cell materials, and in particular relates to a perovskite film and a preparation method thereof, and a perovskite solar cell. Background Art
[0002] Perovskite is a type of semiconductor material with uniform size and high color purity. Its elemental composition is similar to that of the mineral CaTiO 3 Similar crystal structure, is a very promising photovoltaic material. Perovskite materials have strong light absorption ability and wide absorption range, and have great advantages in the field of optoelectronics. For example, perovskite solar cells (PSCs) with perovskite materials as light absorption layer are developing rapidly. They have excellent carrier mobility, high absorption coefficient and low-cost solution processing, and have attracted widespread attention from the business community.
[0003] The solution-based synthesis of perovskites has a good power conversion efficiency (PCE). However, the aprotic polar solvents used to prepare perovskites, such as dimethylformamide (DMF), dimethyl sulfoxide (DMSO), and N-methyl-2-pyrrolidone (NMP), are usually skin penetrating and carcinogenic. The toxicity of these solvents in the perovskite production process can adversely affect the health of manufacturing workers, hinder industrial production, and bring environmental pollution risks. Therefore, from the perspective of green chemistry, the preparation of perovskites by aqueous synthesis has been applied.
[0004] The current method of synthesizing perovskites in water is to make a divalent inorganic salt film from a divalent inorganic salt aqueous solution system, and then convert it into an organic-inorganic hybrid perovskite through a solid-liquid reaction system. However, the exchange of monovalent cations during this conversion process is prone to uneven exchange, which affects the performance of the final perovskite film. Summary of the invention
[0005] The purpose of the present application is to provide a perovskite film and a preparation method thereof, and a perovskite solar cell, aiming to solve the technical problem of how to make the perovskite monovalent cations in the perovskite film uniformly distributed to improve its performance.
[0006] In order to achieve the above application purpose, the technical solution adopted in this application is as follows:
[0007] In a first aspect, the present application provides a method for preparing a perovskite film, comprising:
[0008] preparing a divalent inorganic salt aqueous solution, wherein the divalent inorganic salt in the divalent inorganic salt aqueous solution is an inorganic salt corresponding to the divalent cation of the perovskite;
[0009] Processing the divalent inorganic salt aqueous solution into a film to obtain a divalent inorganic salt film;
[0010] The divalent inorganic salt film is immersed in a methylammonium halide solution, and after drying, coated with a solution containing formamidine halide salt for annealing to obtain a perovskite film containing organic-inorganic hybrid perovskite;
[0011] The methyl amine halide solution contains linear alkyl ammonium halide with 2 to 5 carbon atoms.
[0012] In some embodiments, the linear alkyl ammonium halide includes at least one of ethylammonium chloride, propylammonium chloride, and butylammonium chloride.
[0013] In some embodiments, the molar ratio of the methylammonium halide to the linear alkylammonium halide in the methylammonium halide solution is (5-6):1;
[0014] And / or the concentration of methylammonium halide in the methylammonium halide solution is 8-12 mg / mL.
[0015] In some embodiments, the methylammonium halide in the methylammonium halide solution includes methylammonium iodide and methylammonium chloride in a molar ratio of (3.5-4.5):1;
[0016] And / or, the solution containing formamidine halide salt contains formamidine iodide and methylammonium iodide dissolved in a molar ratio of (7-10):1.
[0017] In some embodiments, the soaking treatment includes the following steps multiple times: soaking for 4 to 5 minutes and then drying with nitrogen;
[0018] And / or, the annealing treatment time is 140-160°C.
[0019] In some embodiments, the solvent in the methylammonium halide solution is an alcohol solvent, and the solvent in the solution containing the formamidine halide salt is an alcohol solvent.
[0020] In some embodiments, in the divalent inorganic salt aqueous solution, the concentration of the divalent inorganic salt is 1.0 to 2.0 mol / L;
[0021] And / or, the divalent inorganic salt includes at least one of nitrate and acetate corresponding to the divalent cation of the perovskite.
[0022] In some embodiments, the step of subjecting the divalent inorganic salt aqueous solution to film-forming treatment includes: coating the divalent inorganic salt aqueous solution to film-forming treatment under the conditions of relative humidity <10% and temperature <20° C., and then performing a drying treatment.
[0023] In a second aspect, the present application provides a perovskite film prepared by the preparation method provided in the first aspect of the present application.
[0024] In a third aspect, the present application provides a perovskite solar cell, comprising the perovskite film provided in the second aspect of the present application.
[0025] The first aspect of the present application provides a method for preparing a perovskite film. A divalent inorganic salt film is immersed in a methylammonium halide solution to generate a methylamine perovskite. Then, a solution containing a formamidinium halide salt is coated for annealing. Methylamine ions and formamidinium ions are exchanged in a solid-liquid system. Since the previous methylammonium halide solution contains a linear alkyl ammonium halide of 2 to 5 carbon atoms, the linear alkyl ammonium halide decomposes into an alkylamine with a higher boiling point than methylamine during the subsequent annealing process. This promotes the top-down diffusion of formamidinium ions in the solid-liquid system. The exchange process achieves homogenization of the formamidinium ion and methylamine ion components, thereby promoting the uniformity of the aqueous organic-inorganic hybrid perovskite components. The perovskite film obtained in this way shows a larger grain size, a lower charge trap density and a longer carrier lifetime, and can be well used in solar cells.
[0026] The perovskite film provided in the second aspect of the present application is prepared by the preparation method provided in the first aspect of the embodiment of the present application. Therefore, the monovalent organic cations in the perovskite film of the present application are evenly distributed, have a lower charge trap density and a longer carrier lifetime, and can be well used in solar cells.
[0027] The perovskite solar cell provided in the third aspect of the present application includes the perovskite film provided in the second aspect of the present application. Based on the advantages of the perovskite film, the perovskite solar cell of the present application has good conversion efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0029] Figure 1 is an XRD diagram of the perovskite film provided in the embodiments of the present application; wherein MAX+EA corresponds to the perovskite film in the perovskite solar cell of Embodiment 1, MAX+PA corresponds to the perovskite film in the perovskite solar cell of Embodiment 2, MAX+BA corresponds to the perovskite film in the perovskite solar cell of Embodiment 3, and MAX corresponds to the perovskite film in the perovskite solar cell of Embodiment 1;
[0030] Figure 2is a microscopic morphology of the perovskite film provided in the embodiments of the present application; wherein MAX+EA corresponds to the perovskite film in the perovskite solar cell of embodiment 1, MAX+PA corresponds to the perovskite film in the perovskite solar cell of embodiment 2, MAX+BA corresponds to the perovskite film in the perovskite solar cell of embodiment 3, and MAX corresponds to the perovskite film in the perovskite solar cell of embodiment 1;
[0031] Figure 3 It is a photovoltaic efficiency diagram of a perovskite solar cell device provided in an embodiment of the present application; wherein MAX+PA corresponds to the perovskite solar cell efficiency curve of Example 2, and MAX corresponds to the perovskite solar cell efficiency curve of Example 1. DETAILED DESCRIPTION
[0032] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0033] In this application, the term "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural. The character " / " generally indicates that the associated objects are in an "or" relationship.
[0034] In the present application, "at least one" means one or more, "more than one" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single or plural items.
[0035] It should be understood that in the various embodiments of the present application, the size of the serial numbers of the above-mentioned processes does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.
[0036] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "said" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0037] The weight of the relevant components mentioned in the embodiment description of the present application can not only refer to the specific content of each component, but also represent the proportional relationship between the weights of the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the embodiment description of the present application, it is within the scope disclosed in the embodiment description of the present application. Specifically, the mass described in the embodiment description of the present application can be a mass unit known in the chemical industry such as μg, mg, g, kg, etc.
[0038] The terms "first" and "second" are used only for descriptive purposes to distinguish objects such as substances from each other, and should not be understood as indicating or implying relative importance or implicitly indicating the number of indicated technical features. For example, without departing from the scope of the embodiments of the present application, the first XX may also be referred to as the second XX, and similarly, the second XX may also be referred to as the first XX. Thus, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features.
[0039] The photoelectric conversion efficiency of organic-inorganic hybrid perovskite solar cells has been significantly improved. From the perspective of green chemistry, the use of water solvents to synthesize materials is the most ideal and environmentally friendly. Therefore, the use of divalent inorganic salt aqueous solutions (e.g., lead nitrate aqueous precursor solutions) to prepare perovskites has been well applied.
[0040] After the divalent inorganic salt aqueous solution system is made into a divalent inorganic salt film, it is then converted into an organic-inorganic hybrid perovskite through a solid-liquid reaction system. However, during this conversion process, if the MA-FA cation is exchanged during the annealing process, + In comparison, FA + The diffusion rate is slow, and the perovskite film will have an uneven distribution of monovalent cations, that is, there is still a certain amount of FA + and MA + They are respectively enriched on the upper surface of the film and the buried interface. This will cause the generation of lattice stress and energy level mismatch at the perovskite / electron transport layer interface, hindering carrier transport and ultimately restricting the device PCE.
[0041] Based on this, the embodiment of the present application proposes to introduce a linear alkyl ammonium halide with a certain number of carbon atoms, and immerse the divalent inorganic salt membrane in a methyl ammonium halide solution, wherein the methyl ammonium halide solution contains a linear alkyl ammonium halide with 2 to 5 carbon atoms, so that the monovalent cation component of the aqueous perovskite generated during subsequent annealing can be more uniform. The specific technical solution is as follows.
[0042] In a first aspect, an embodiment of the present application provides a method for preparing a perovskite film. Specifically, the preparation method of the embodiment of the present application includes:
[0043] S01: preparing a divalent inorganic salt aqueous solution, wherein the divalent inorganic salt in the divalent inorganic salt aqueous solution is an inorganic salt corresponding to the divalent cation of the perovskite;
[0044] S02: subjecting the divalent inorganic salt aqueous solution to a film-forming treatment to obtain a divalent inorganic salt film;
[0045] S03: placing the divalent inorganic salt film in a methyl ammonium halide solution for immersion treatment, and after drying, coating it with a solution containing formamidine halide salt for annealing treatment to obtain a perovskite film containing organic-inorganic hybrid perovskite; wherein the methyl ammonium halide solution contains a linear alkyl ammonium halide with 2 to 5 carbon atoms.
[0046] The embodiment of the present application is based on the fact that the methylamine halide solution contains straight-chain alkyl ammonium halides of 2 to 5 carbon atoms. In the subsequent annealing process, the straight-chain alkyl ammonium halides are decomposed into alkylamines with higher boiling points than methylamine, thereby promoting the top-down diffusion of formamidinium ions in the solid-liquid system. The exchange process achieves the homogenization of the formamidinium ion and methylamine ion components, thereby promoting the uniformity of the aqueous organic-inorganic hybrid perovskite components. The perovskite film obtained in this way shows a larger grain size, a lower charge trap density and a longer carrier lifetime.
[0047] In step S01, the divalent inorganic salt in the divalent inorganic salt aqueous solution is an inorganic salt corresponding to the divalent cation of the perovskite. For example, the chemical formula of the organic-inorganic hybrid perovskite material can be ABM 3 ; Wherein, A is a monovalent organic cation, which may include CH 3 NH 3 + (MA + ), CH(NH 2 ) 2 + (FA + ), B is a divalent metal cation, specifically Pb 2+ Sn 2+ At least one of; M is a monovalent anion, specifically a halogen ion, including Cl - Br - and I - At least one of .
[0048] For example, the divalent metal ions in the organic-inorganic hybrid perovskite may be lead ions or tin ions, and the divalent inorganic salt may be a lead salt or a tin salt. Specifically, they may be the corresponding acetates or nitrates, for example, the lead salt may be lead nitrate or lead acetate, and the tin salt may be tin nitrate or tin acetate.
[0049] The preparation step of the divalent inorganic salt aqueous solution may be: adding the divalent inorganic salt into water and dissolving it to obtain the divalent inorganic salt aqueous solution.
[0050] In some embodiments, the concentration of the divalent inorganic salt in the divalent inorganic salt aqueous solution is 1.0-2.0 mol / L.
[0051] Step S02 is a film-forming process of a divalent inorganic salt aqueous solution.
[0052] In some embodiments, the step of film-forming treatment with the divalent inorganic salt aqueous solution comprises: coating the divalent inorganic salt aqueous solution to form a film under the conditions of relative humidity <10% and temperature <20° C., and then performing a drying treatment.
[0053] In some embodiments, the temperature of the divalent inorganic salt aqueous solution after coating is 80-100° C. and the time is 20-40 minutes. Under the above conditions, the aqueous solvent can be dried well.
[0054] Step S03 is an organic-inorganic hybrid perovskite generation step.
[0055] First, the divalent inorganic salt film is placed in a methylammonium halide solution for immersion treatment to obtain a methylamine perovskite, and then coated with a solution containing a formamidinium halide salt for annealing treatment after drying to obtain a formamidinium-based organic-inorganic hybrid perovskite. In this process, the divalent inorganic salt film is first converted into a methylamine perovskite, and then converted into a formamidinium-based organic-inorganic hybrid perovskite through the exchange of monovalent ions, and the required formamidinium-based organic-inorganic hybrid perovskite can be obtained according to the configuration of monovalent cations in the solution containing the formamidinium halide salt, for example, it can be a formamidinium-methylamine-based (different stoichiometric ratio) organic-inorganic hybrid perovskite. Among them, the methylammonium halide solution contains a linear alkyl ammonium halide of 2 to 5 carbon atoms, and the halogen atoms can be chlorine, bromine, iodine, etc.
[0056] In some embodiments, the linear alkyl ammonium halide includes at least one of ethyl ammonium halide, propyl ammonium halide, and butyl ammonium halide, such as at least one of ethyl ammonium chloride, propyl ammonium chloride, and butyl ammonium chloride.
[0057] The above linear alkyl ammonium halides can spontaneously decompose into alkylamine and HCl (deprotonation) during annealing. For example, ethylammonium chloride decomposes into ethylamine and HCl, propylammonium chloride decomposes into propylamine and HCl, and butylammonium chloride decomposes into butylamine and HCl.
[0058] Methylamine, vapor pressure 186.1kPa, boiling point -6.6℃; ethylamine, vapor pressure 121.1kPa, boiling point 17℃; propylamine, vapor pressure 33.01.1kPa, boiling point 47~51℃; butylamine, vapor pressure 9.07kPa, boiling point 77~79℃. Compared with methylamine, which evaporates at room temperature, the presence of ethylamine, propylamine and butylamine with higher boiling points will carry FA +It fully diffuses from top to bottom along the grain boundary. This solid-liquid diffusion promotes full exchange of FA-MA. The slow decomposition and volatilization of linear alkyl ammonium halides can prolong the FA-MA exchange time and make FA more evenly distributed in the film. It should be noted that the implementation of this application has found through research that if the above-mentioned linear alkyl ammonium halide is not added to the methyl ammonium halide solution, but is added to the subsequent solution containing formamidine halide salt, and is deposited on the surface of MA-based perovskite by spin coating, due to the large size of the alkylamine ions in the linear alkyl ammonium halide and the slow diffusion rate, the spin coating step makes it difficult for the linear alkyl ammonium halide to be evenly distributed from top to bottom at the perovskite grain boundary. It is only distributed on the upper surface and cannot play a mediating role during the annealing process, resulting in FA + Therefore, in the preparation method of the embodiment of the present application, the linear alkyl ammonium halide is added to the methyl ammonium halide solution.
[0059] In some embodiments, the molar ratio of methylammonium halide to linear alkylammonium halide in the methylammonium halide solution is (5-6):1, and the concentration of methylammonium halide in the methylammonium halide solution is 8-12 mg / mL. At this concentration, linear alkylammonium halide has a good regulating effect.
[0060] In some embodiments, each soaking treatment lasts for 4 to 5 minutes, and nitrogen is blown dry after each soaking for 4 to 5 minutes; specifically, the soaking can be performed 3 to 4 times. In this way, methylamine perovskite can be fully converted.
[0061] In some embodiments, the annealing treatment time is 140-160° C. Under this condition, the formamidinium-based perovskite can be fully converted into a formamidinium-based organic-inorganic hybrid perovskite.
[0062] Specifically, the methylammonium halide solution contains methylammonium iodide (MAI) and methylammonium chloride (MACl) in a molar ratio of (3.5-4.5):1; the solution containing formamidinium halide contains formamidinium iodide (FAI) and methylammonium iodide (MAI) in a molar ratio of (7-10):1, and the finally obtained formamidinium-based organic-inorganic hybrid perovskite can contain both formamidinium-based and methylamine-based organic-inorganic hybrid perovskites. Furthermore, methylammonium chloride (MACl) is also dissolved in the solution containing formamidinium halide. In the methylammonium halide solution and the solution containing formamidinium halide, the solvent can be an alcohol solvent, such as isopropyl alcohol (IPA).
[0063] Furthermore, a passivation agent may be spin-coated on the surface of the perovskite film. For example, a passivation agent solution (the passivation agent is phenylethylamine iodide PEAI, the solvent is isopropanol, and the concentration is 4-6 mg / mL) is spin-coated on the surface of the perovskite film and then dried.
[0064] In the second aspect, the embodiment of the present application provides a perovskite film. That is, the perovskite film of the embodiment of the present application is prepared by the preparation method provided by the first aspect of the embodiment of the present application. The perovskite film of the embodiment of the present application has a uniform distribution of monovalent organic cations, a low charge trap density and a long carrier lifetime, and can be well used in solar cells.
[0065] In a third aspect, an embodiment of the present application provides a perovskite solar cell. The perovskite solar cell of the embodiment of the present application includes the perovskite film provided in the second aspect of the present application.
[0066] The perovskite solar cell provided in the third aspect of the present application includes the perovskite film provided in the second aspect of the present application. Based on the advantages of the perovskite film, the perovskite solar cell of the present application has good conversion efficiency.
[0067] Specifically, the perovskite solar cell of the embodiment of the present application includes a first electrode, a second electrode and a perovskite layer located between the first electrode and the second electrode, an electron transport layer is arranged between the perovskite layer and the first electrode, and the perovskite layer is the perovskite film obtained by the above-mentioned preparation method of the embodiment of the present application.
[0068] In some embodiments, the electron transport layer may be a metal oxide or a doped metal oxide. For example, the metal oxide may include TiO 2 、meso-TiO 2 、NiOx、SnO 2 、ZrO 2 , ZnO, and the embodiment of the present application can use titanium dioxide and lithium-doped titanium dioxide. The electron transport layer can be a layer of metal oxide or two stacked layers of metal oxide.
[0069] In some embodiments, the first electrode may be a transparent conductive substrate, including but not limited to the following materials: fluorine-doped tin oxide (FTO), indium-doped tin oxide (ITO), aluminum-doped zinc oxide (AZO), boron-doped zinc oxide (BZO), indium-doped zinc oxide (IZO), etc. The second electrode may be a metal top electrode, such as gold, silver, copper, etc., or one or more of the conductive oxide electrodes.
[0070] The preparation method of the above-mentioned perovskite solar cell includes: 1) preparing an electron transport layer on the first electrode; 2) preparing a perovskite layer on the electron transport layer, that is, the preparation method provided in the first aspect of the embodiment of the present application can be used to prepare a perovskite film; 3) preparing a second electrode on the perovskite layer. Through this method, a perovskite film with uniform distribution of monovalent organic cations can be prepared on the electron transport layer. In the preparation process of the perovskite film, during the divalent inorganic salt / perovskite conversion process, a linear alkyl ammonium halide (such as ethylammonium chloride EACl, propylammonium chloride PACl or butylammonium chloride BACl) is introduced into a methylammonium halide solution for immersion, and the subsequent coating of the solution containing formamidine halide salt annealing process promotes FA-MA cation exchange, and promotes the uniform distribution of monovalent cations of the aqueous perovskite by means of the mediation of long-chain alkyl ammonium chloride.
[0071] In some embodiments, a hole transport layer may be provided between the perovskite layer and the second electrode to further improve the hole transport performance of the perovskite solar cell. Specifically, the material of the hole transport layer may include 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (Spiro-OMeTAD), poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] (PTAA), poly-3-hexylthiophene (P3HT), triphenylamine (H101) with triptycene as the core, 3,4-ethylenedioxythiophene-methoxytriphenylamine (EDOT-OMeTPA), N-(4-aniline)carbazole-spirobifluorene (CzPAF-SBF), poly(3,4-ethylenedioxythiophene):poly(styrene sulfonate) (PEDOT:PSS), etc.
[0072] The following describes the invention in conjunction with specific embodiments.
[0073] Example 1
[0074] A perovskite solar cell comprises, in sequence: an FTO glass substrate, an electron transport layer, a perovskite layer, a hole transport layer, and a top electrode. The preparation method is as follows:
[0075] 1) FTO glass substrate pretreatment
[0076] The FTO glass was ultrasonically cleaned with glass cleaning solution, deionized water, and ethanol for 15 minutes respectively, and then dried with nitrogen flow. 3 Process for 20 minutes.
[0077] 2) Preparation of electron transport layer
[0078] The pretreated FTO glass substrate was placed in a culture dish: 40 mM titanium tetrachloride aqueous solution was added, and the dish was placed in a 70° C. oven for 1 hour to obtain a dense titanium dioxide layer with a thickness of 40 nm.
[0079] The substrate prepared with the dense titanium dioxide layer was rinsed and dried with water, and the titanium dioxide slurry (the particle size of the titanium dioxide particles was about 30 nm) was diluted with anhydrous alcohol at a mass ratio of 7:1, and stirred for 12 hours to form a stable suspension; the suspension was coated on the substrate with an initial rotation speed of 5000 revolutions per second (r / s), an acceleration of 1000 r / s, a spin coating time of 30 seconds, and then annealed at 500°C for half an hour to obtain a porous titanium dioxide layer with a thickness of 200 nm.
[0080] The substrate was then placed in a culture dish, 20 mM titanium tetrachloride solution was added, and the substrate was kept in an oven at 70°C for 30 minutes. After being washed with water and blown dry, a lithium carbonate aqueous solution (concentration 2 mg / mL) was spin-coated on the substrate at a speed of 3000 r / s for 30 seconds, and annealed at 450°C for half an hour to obtain the final electron transport layer.
[0081] 3) Preparation of perovskite layer
[0082] 3.1 Lead nitrate film: first prepare an aqueous solution of lead nitrate; add lead nitrate to 1 ml of water, stir to dissolve and then filter to obtain an aqueous solution of lead nitrate with a concentration of 1.5 M; spin coat the aqueous solution of lead nitrate on the electron transport layer, control the ambient humidity and temperature during the process, and carry out under low humidity conditions (RH=5%, temperature=15°C), dynamically spin coat the aqueous solution of lead nitrate at 5000 r / s, and then bake at 100°C for 30 minutes to obtain a transparent white lead nitrate film with a thickness of about 350 nm.
[0083] 3.2 Conversion of aqueous perovskite: First, the lead nitrate film is converted into MA-based perovskite by multiple immersions. Specifically, ethylammonium chloride is added to a methylamine halide solution (containing MAI and MACl, with a molar ratio of MAI:MACl=4:1, the solvent is IPA, and the total concentration of methylamine halide is 10 mg / mL), and the amount of ethylammonium chloride added is 1 / 5 of the total molar amount of methylammonium halide; then, the lead nitrate film substrate is immersed in the methylamine halide solution with ethylammonium chloride for 4 minutes, taken out and rinsed with IPA, dried with nitrogen and immersed again, and this process is repeated four times to obtain MA-based perovskite. Subsequently, a solution containing a high concentration of formamidinium halide was prepared (containing: 155 mg FAI, 15 mg MAI, 20 mg MACl, and 3.2 mL IPA as solvent), and the FAI-containing solution (about 200 μL) was dynamically spin-coated on the surface of the MA-based perovskite at 3000 r / s, and annealed at 150°C for 15 minutes (RH about 30-40%) to obtain a perovskite film with a thickness of 500 nm.
[0084] Spin coating of passivation agent: Spin coating of passivation agent solution (the passivation agent is PEAI, the solvent is IPA, and the passivation agent concentration is 5 mg / mL) on the surface of the perovskite film at 5000 r / s, and then drying the solvent.
[0085] 4) Preparation of hole transport layer
[0086] 72.3 mg of Spiro-OMeTAD, 28.6 μL of 4-tert-butylpyridine, and 18.6 μL of Li-TFSI acetonitrile solution (concentration of 520 mg / mL) were added to 1 mL of chlorobenzene, stirred for 12 hours, and then spin-coated on the perovskite surface at a speed of 5000 r / s for 30 seconds to obtain a hole transport layer with a thickness of about 200 nm.
[0087] 5) Top electrode preparation
[0088] The gold electrode is evaporated to a thickness of about 80nm.
[0089] Example 2
[0090] A perovskite solar cell and a preparation method thereof, which differs from Example 1 in that: in the preparation of the perovskite layer, the linear alkyl ammonium halide added to the methyl ammonium halide solution is propyl ammonium chloride, and the rest is the same as Example 1.
[0091] Example 3
[0092] A perovskite solar cell and a preparation method thereof, which differs from Example 1 in that: in the preparation of the perovskite layer, the linear alkyl ammonium halide added to the methyl ammonium halide solution is butyl ammonium chloride, and the rest is the same as Example 1.
[0093] Comparative Example 1
[0094] A perovskite solar cell comprises, in sequence: an FTO glass substrate, an electron transport layer, a perovskite layer, a hole transport layer, and a top electrode. The difference between the preparation method thereof and that of Example 1 is that in the preparation of the perovskite layer, no linear alkyl ammonium halide: ethyl ammonium chloride is added to the methyl ammonium halide solution, and the rest is the same as that of Example 1.
[0095] Performance Testing
[0096] like Figure 1 The XRD data of the perovskite films of the embodiments and comparative examples show that in Examples 1-3, the introduction of ethylammonium chloride, propylammonium chloride or butylammonium chloride in the methylammonium halide solution was proven to increase the intensity of the final aqueous perovskite (100) diffraction peak and reduce its half-height width, confirming that the use of the above-mentioned straight-chain alkyl ammonium halide can effectively improve the crystallinity of the perovskite, among which propylammonium chloride (PACl) in Example 2 has the best effect.
[0097] like Figure 2The electron scanning microscope (SEM) shows that the initial perovskite morphology of Comparative Example 1 has a small grain size, while the addition of the above-mentioned linear alkyl ammonium halide in Examples 1-3 further increases the grain size of the formed perovskite film and makes the size distribution more uniform. The introduction of the above-mentioned linear alkyl ammonium halide can significantly promote the growth of perovskite grains, and a high-quality perovskite film with a low grain boundary defect density can be obtained.
[0098] In addition, the results of testing the photovoltaic efficiency of perovskite solar cell devices show that the introduction of the linear alkyl ammonium halides of Examples 1-3 can improve the photoelectric conversion efficiency of the aqueous perovskite solar cell devices, among which Example 2 has the best effect. Figure 3 As shown, the content of carbon dioxide in comparative example 1 can be increased from 20.78% in comparative example 1 to 23.88% in example 2.
[0099] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.
Claims
1. A method for preparing a perovskite film, characterized in that: include: preparing a divalent inorganic salt aqueous solution, wherein the divalent inorganic salt in the divalent inorganic salt aqueous solution is an inorganic salt corresponding to the divalent cation of the perovskite; subjecting the divalent inorganic salt aqueous solution to a film-forming treatment to obtain a divalent inorganic salt film; The divalent inorganic salt film is immersed in a methylammonium halide solution, and after drying, coated with a solution containing formamidine halide salt for annealing to obtain a perovskite film containing organic-inorganic hybrid perovskite; The methyl amine halide solution contains linear alkyl ammonium halide with 2 to 5 carbon atoms.
2. The preparation method according to claim 1, characterized in that The linear alkyl ammonium halide includes at least one of ethylammonium chloride, propylammonium chloride and butylammonium chloride.
3. The preparation method according to claim 1, characterized in that: The molar ratio of the methylammonium halide to the linear alkylammonium halide in the methylammonium halide solution is (5-6):1; And / or the concentration of methylammonium halide in the methylammonium halide solution is 8-12 mg / mL.
4. The preparation method according to claim 1, characterized in that: The methylammonium halide in the methylammonium halide solution includes methylammonium iodide and methylammonium chloride in a molar ratio of (3.5-4.5):1; And / or, the solution containing formamidine halide salt contains formamidine iodide and methylammonium iodide dissolved in a molar ratio of (7-10):
1.
5. The preparation method according to claim 1, characterized in that: The soaking treatment includes the following steps for multiple times: soaking for 4 to 5 minutes and then drying with nitrogen; And / or, the annealing treatment time is 140-160°C.
6. The preparation method according to any one of claims 1 to 5, characterized in that: The solvent in the methylammonium halide solution is an alcohol solvent, and the solvent in the solution containing formamidine halide is an alcohol solvent.
7. The preparation method according to any one of claims 1 to 5, characterized in that: In the divalent inorganic salt aqueous solution, the concentration of the divalent inorganic salt is 1.0 to 2.0 mol / L; And / or, the divalent inorganic salt includes at least one of nitrate and acetate corresponding to the divalent cation of the perovskite.
8. The preparation method according to any one of claims 1 to 5, characterized in that: The step of film-forming the divalent inorganic salt aqueous solution comprises: coating the divalent inorganic salt aqueous solution to form a film under the conditions of relative humidity <10% and temperature <20°C, and then performing a drying treatment.
9. A perovskite film, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 8.
10. A perovskite solar cell, characterized in that: Comprising the perovskite film as described in claim 9.
Citation Information
Patent Citations
In-situ-generation-based passivation layer with water stability and thermal stability and perovskite solar cell with passivation layer
CN113224239A
A formamidinium-based organic / inorganic perovskite solar cell and its fabrication method
CN114937743A
Perovskite thin film and preparation method and application thereof
CN116367674A
Perovskite solar cell and manufacturing method of perovskite thin film
CN118284279A
KR20230156478A